Peran Sosial Media dalam Perkembangan Pemasaran Digital : A Systematic Literature Review - Faisal Reza; Ira Valentina Silalahi (Jurnal Dimamu, 2023)
The main problem in marketing communications is the communication channels that can be used in marketing programs. The purpose of this research is to answer the question of how the role of social media Instagram on the development of digital marketing. This research applies the Systematic Literature Review method. Based on the results, the researcher found 136 Scopus articles in a search using Publish or Perish and the help of other applications such as Zotero, Mendeley, VOSViewer, and Microsoft Excel which were then filtered into 55 selected articles for descriptive analysis. The findings show that social media Instagram has contributed to the development of digital marketing. Social media Instagram has played a role as a marketing communication medium, increasing brand awareness, influencing consumer engagement and behavior, and generating data that supports marketing strategies.